If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11w + 7)(4w + -12) = 0 Reorder the terms: (7 + 11w)(4w + -12) = 0 Reorder the terms: (7 + 11w)(-12 + 4w) = 0 Multiply (7 + 11w) * (-12 + 4w) (7(-12 + 4w) + 11w * (-12 + 4w)) = 0 ((-12 * 7 + 4w * 7) + 11w * (-12 + 4w)) = 0 ((-84 + 28w) + 11w * (-12 + 4w)) = 0 (-84 + 28w + (-12 * 11w + 4w * 11w)) = 0 (-84 + 28w + (-132w + 44w2)) = 0 Combine like terms: 28w + -132w = -104w (-84 + -104w + 44w2) = 0 Solving -84 + -104w + 44w2 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '4'. 4(-21 + -26w + 11w2) = 0 Factor a trinomial. 4((-7 + -11w)(3 + -1w)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-7 + -11w)' equal to zero and attempt to solve: Simplifying -7 + -11w = 0 Solving -7 + -11w = 0 Move all terms containing w to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -11w = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -11w = 0 + 7 -11w = 0 + 7 Combine like terms: 0 + 7 = 7 -11w = 7 Divide each side by '-11'. w = -0.6363636364 Simplifying w = -0.6363636364Subproblem 2
Set the factor '(3 + -1w)' equal to zero and attempt to solve: Simplifying 3 + -1w = 0 Solving 3 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1w = 0 + -3 -1w = 0 + -3 Combine like terms: 0 + -3 = -3 -1w = -3 Divide each side by '-1'. w = 3 Simplifying w = 3Solution
w = {-0.6363636364, 3}
| 16=x/6 | | -4(10-2y)=-(-5y+7) | | 10(p+9)=8(p+7) | | -44-4x=-3(x+12) | | 8(10+2n)=-2-(2-10n) | | 2y(n+4)=5y | | 3-8x+16x^2= | | -8+8m=8(m-2)+8 | | 9p+9=2(-2+4p) | | -35+9v=-(7-5v) | | 6(9y-8)=46+7y | | 112x^2-56x+21= | | -6x-26=7(7-3x) | | 4(v+9)-5v=43-v | | 2+2=d | | -8(-3x-9)-8=10x-20 | | 0.7x+12.8=x-1.93 | | r^2-5r+1=0 | | 2(2x-3.8)=8x-7.6 | | 10(2p+5)=-15+7p | | -0.6x+3.97=-0.8x+2.37 | | -5(x-4)+10=45-10x | | 6.6+0.9x=0.3 | | -2w-9(6-10w)=29+5w | | 10x-10=5x-2 | | 7x^4-13x^2-15= | | 6+2(9+4x)=5x+3 | | x^3-4x^2-11x=-30 | | BD=2(a+1) | | 3+4ab-9b^2= | | 3(x+2.64)=2x | | AC=2(5a+1) |